Influencia del empaquetamiento granular en el módulo resiliente de las mezclas asfálticas en caliente (2016)
Grain-size measurement is an important requirement in the design of asphalt mixes as its mechanical and dynamic characteristics add frictional resistance which contributes to stability.  Grain-size measurement is a relatively easy to control variable and in the INVÍAS specifications for construction of roads it is recommended to evaluate granular packaging according to the Bailey method and report the results, but it is not a requirement for acceptance or denial of the mix design.  The resilient module is a parameter required for design mix  verification and for dimensioning pavement structures.  This article presents the experimental results of the analysis of granular packaging with the three parameters of the Bailey method for different asphalt mixes made with materials from the region of  Boyacá, using three gradations within the grain-size range of an MDC-19 and three within the range of SUPERWAVE. The mixes were designed with the Marshall method accelerated by RAMCODES and the resilient modules were determined with NAT laboratory equipment.  The results are compared using statistical analysis of variance and box diagrams to determine if there are significant differences and decide whether granular packaging influences the magnitude of the resilient modules or not.  As a result of the study, it is determined that the difference between the resilient modules is significant with a confidence level greater than 95%.